CRITICISM OF INTERFAITH MARRIAGE IN RELIGIOUS MODERATION - M. Imam Syafi'i; Samsul Ariyadi; Ade Naelul Huda (JCI Publisher, 2026)
This article examines criticism of the practice of interfaith marriage in the framework of religious moderation in Indonesia over the past fifteen years. Through a qualitative approach with a structured literature study, this study evaluates the dynamics of interfaith marriage criticism and its impact on religious moderation practices in society. Data was collected from journals and books published between 2018 and 2023 that discussed the theory of religious moderation and the dynamics of interfaith marriage. The results of the analysis show that criticism of interfaith marriage, while potentially hindering tolerance, also triggers negotiations of religious identity and renewal of the value of moderation. These findings reveal a new understanding that criticism, when articulated in a balanced and objective manner, can encourage the enhancement of intercommunal dialogue and the affirmation of the values of religious moderation. The implications of this research are important in the development of inclusive public policy and religious practices, and are expected to serve as a basis for further research and decision-making in the fields of religious moderation and socio-religious studies.